The effect of distal radius fractures involving the distal radioulnar articular joint on forearm rotation - Lingde Kong (Journal of Orthopaedic Surgery and Research, 2020)
Abstract Background The objective of this study was to predict the function of the forearm rotation on the basis of the articular surface of the sigmoid notch from three-dimensional reconstruction images. Methods We retrospectively reviewed patients who underwent volar plate fixation for intra-articular distal radius fractures (DRFs) in our institution between January 2017 and July 2019. The 3D image of the sigmoid notch on the fractured distal radius was reconstructed and looked up from the ulnar view to determine the existence of gaps or steps. Patients with or without gaps/steps on the sigmoid notch were included in the case group or control group, respectively. The patients’ basic data and postoperative data were collected and compared. Results A total of 81 patients were included. There were 33 patients in the case group, and 48 patients in the control group. There was no significant difference between the two groups at baseline. The total range of motion (ROM) of rotation in the case group and control group was 130.3 ± 6.2° and 145.3 ± 6.7°, respectively (P < 0.001). The percentage of rotation ROM of contralateral limb in the case group and control group was 72.3 ± 3.1% and 80.7 ± 3.6%, respectively (P < 0.001). VAS during forearm rotation was 2.1 ± 0.7 in the case group, which is significantly higher than that in the control group (1.5 ± 0.5, P < 0.001). Conclusion This study proposed a new method to assess the articular surface of the sigmoid notch which is based on 3D reconstruction images. With the assistance of this method, we found that gaps or steps on the sigmoid notch not only limit forearm pronation rotation and supination rotation, but also cause apparent wrist pain during forearm rotation movement and poor wrist ability.